(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the main work performed on the maintenance, restoration and repair of emerging malfunctions of plain bearings. Wear of the rubbing surfaces of plain bearings causes their geometric shape to be disturbed and marks and scuffs appear; the bore becomes oval. Wear is sometimes so great that the lubrication grooves of the bearings almost lose their outlines, and it becomes impossible to adjust the interference to compensate for wear.